Coordinación interinstitucional de los servicios de atención a la pequeña infancia en La Rioja - Silvia Sastre i Riva; Felisa Bonachía Caballero (Universidad de La Rioja, 2007)
The aim of this work is knowing the state of the art of the coordination measures among the Early Infancy Intervention Centers in the La Rioja's region. Materials and method: data was extracted by a mixed questionnary constructed "ad hoc" and administered to n= 47 professionals of Early Interventional Centres distributed according their geographical location: Rioja Alta, Rioja Centro, Rioja Baja. Significant differences among answers obtained was calculated using the SPSS program (p0.005) in relation to the conceptual axis designed. Results show that: a) coordination among professionals is made by their own initiative in order to discuss individual treatments programmed; b) interventional procedures are best coordinated, significantly, among the professionals in the same interventional center; c) public resources distribution is differential, irregular and insufient relating to the geographical location; d) knowing of the working objectives and functions of other early interventional centers are unknown; e) there is a lack of organization among them, Conclusion: the current structure of the Early Interventional Centers in La Rioja is poorly organized; oficial regulated coordination is necessary.